Inequalities in the provision of paediatric speech and language therapy services across London boroughs. Issue 4 (27th March 2016) - Pring, Tim
Abstract: Background: The inverse‐care law suggests that fewer healthcare resources are available in deprived areas where health needs are greatest. Aims: To examine the provision of paediatric speech and language services across London boroughs and to relate provision to the level of deprivation of the boroughs. Methods & Procedures: Information on the employment of paediatric speech and language therapists was obtained from London boroughs by freedom‐of‐information requests. The relationship between the number of therapists and the index of multiple deprivation for the borough was examined. Outcomes & Results: Twenty‐nine of 32 boroughs responded. A positive relationship between provision and need was obtained, suggesting that the inverse‐care law does not apply. However, large inequalities of provision were found particularly among the more socially deprived boroughs. In some instances boroughs had five times as many therapists per child as other boroughs. Conclusions & Implications: The data reveal that large differences in speech and language therapy provision exist across boroughs. The reasons for these inequalities are unclear, but the lack of comparative information across boroughs is likely to be unhelpful in planning equitable services. The use of freedom of information in assessing health inequalities is stressed and its future availability is desirable.